Comparison Analysis Operastional Cost of Vehicle (VOC) Between Kayu Agung-Palembang-Betung Toll Road Plan with Existing Road. (November 2019) - Kadarsa, E; Hanafiah,; Adhitya, B B; Pataras, M; Azari, A
Abstract: South Sumatra is one of the provinces whose development is very rapid in Indonesia. With the increasing development of centers of economic activity, politics, socio-culture and education make it an attraction for residents outside the city to travel to Palembang City. However, the condition of the eksisting highway which has become the driver's mainstay for travelling are not free of congestion. This causes travel time and Vehicle operational costs increase for every vehicle that passes the road. To overcome this problem, the government brought investors to build a toll road. The results of preliminary research show that people are still confused about the benefits through toll roads which are built besides travel time faster because they have to spend money to pay tolls. The main objective of this study was to determine the vehicle operating costs (VOC) using both roads with the Pacific Consultant International Method (PCI) and Industrial and Affiliate Research, Bandung Institute of Technology (LAPI ITB). Variable of the equation to determine the cost components is travel speed determined the Floating Car Method. The results show that the operational costs of vehicles (VOC) through toll roads are smaller when compared with existing roads. VOC of passenger cars that pass through the existing road in the morning Rp. 3395.45, trucks 2 axles loaded Rp. 5570.55 and trucks 2 axles with no payload of Rp. 3815.00, while if through toll road, passenger cars Rp. 2618.82 and trucks 2 axles Rp. 2918.71. In addition, information is obtained, more than 90% of drivers only consider fuel costs, they do not consider the cost of other variable variables in choosing a route.